The conservation and sustainable use of agrobiodiversity in China and Germany: Advancing the policy agenda - Sensen, Sarah; Yiching, Song; Vernooy, Ronnie (2024)
One of the areas of work of the Sino-German Agrobiodiversity Network is agrobiodiversity policy development, in particular in support of the efforts of farmers, farming communities, and related organizations to conserve and sustainably use agrobiodiversity. In the context of the Sino-German collaboration, what can the two countries learn from each other to advance the policy agenda for agrobiodiversity? What are today’s challenges and opportunities? This report presents five policy recommendations.